External Funding of Doctoral Education: Background and Reflection - Uller, Tobias (Högre utbildning, 2016)
External funding of doctoral education is becoming increasingly common in Sweden. Here I discuss how this practice may cause tensions between the learning outcomes in the Higher Education Ordinance and the practice of doctoral education. Employment on externally funded projects tend to marginalize some components of education that traditionally have been considered fundamental for third cycle students, and creates more complex roles for both students and supervisor. These can have both positive and negative consequences for student-supervisor relations that warrant further study. The increased reliance on external funding to support students also raises fundamental questions about the form, content, and aims of doctoral education.